The relationship between superior-subordinate communication, LMX quality and employee job satisfaction among hotel employees - Khan, Sanan Waheed (2019)
Despite the abundance of research in the area of supervisory communication, the hotel industry in Malaysia is facing high employee turnover. Therefore, the main purpose of this study is to examine the relationship between superior - subordinate communication and LMX quality with employee job satisfaction in five-star hotels in Langkawi Island, Malaysia. The Leader-Member Exchange (LMX) Theory guided this thesis, which utilized a survey to measure the opinions of the 322 respondents using simple random sampling method. Data was gathered and analyzed using Statistical Package for Social Sciences (SPSS). The data were analyzed using correlation and multiple regression analysis. Results revealed that supervisory communication relationship and LMX quality have significant positive relationship with employee job satisfaction. The current study indicates that good communication between a supervisor and a subordinate will result in greater job satisfaction and better organizational functioning. Furthermore, the present study has suggested few theoretical and practical recommendations to the five-star hotel industry in Langkawi to improve the level of supervisory communication to increase employee job satisfaction. The findings are noteworthy for the industry and also contribute to new empirical findings to the literature on superior - subordinate communication and LMX quality.